Pengaruh Digital Customer Experience dalam Menciptakan Customer Satisfaction dan Customer Loyalty di Era Digital - Sri Rahayu; Sri Tita Faulina (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study are (1) to analyze and find out how the influence of digital customer experience in creating OVO user satisfaction in the digital era; (2) to analyze and find out how the influence of digital customer experience in creating customer loyalty for OVO users in the digital era; and (3) to analyze and find out how the influence of consumer satisfaction on customer loyalty of OVO users in the digital era. The independent variable used is digital customer experience while the dependent variable is customer satisfaction and customer loyalty. The use of data analysis obtained from the object of research using a survey model with a quantitative approach. The number of samples obtained as respondents as many as 110 people. The data for analysis uses validity and reliability tests using the outer model and the SEM structural model as a representative of the inner model. The results of the analysis show that the value of R2 for the consumer satisfaction variable is 40.6% and the consumer loyalty variable is 50.9%, with a significant level of 0.05. The results show that digital customer experience has a positive influence on consumer satisfaction and customer loyalty of OVO users and consumer satisfaction has a positive effect on consumer loyalty of OVO users in the digital era.